Esa Pekka Salonen conducts Debussy, Ravel and Beethoven - Debussy, Claude 1862-1918; Ravel, Maurice 1875-1937; Bach, Johann Sebastian 1685-1750; Beethoven, Ludwig van 1770-1827 (Idéale Audience - 2012, 2012)
Esa-Pekka Salonen conducts the Orchestre de Paris for an exceptional concert with the pianist David Fray. After studying conducting and composition at the Sibelius Academy in Helsinki, Esa-Pekka Salonen became director of the Swedish Radio Symphony Orchestra. He left Europe to become the music director of one of the world's greatest orchestras: the Los Angeles Philharmonic. Thus, Esa-Pekka Salonen made his name as a charismatic director introducing the public to the contemporary music. In this concert, Esa-Pekka Salonen joins forces with the Orchestre de Paris and the rising star of the French ipano David Fray for a programme made up of Debussy's La Mer, Ravel's Concerto in G and Beethoven's Symphony No. 7
Keywords: Concertos (Piano); Suites (Piano); Symphonic poems; Symphonies; Internet videos